Peran Kelompok Bermain El-Diina Sukabumi dalam Meningkatkan Mutu Pendidikan - Salma Tsana Fi Sa’adah; Siti Qomariyah; Vera Siti Magfiroh (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study aims to find out the role of the El-Diina Sukabumi Play Group (KB) in improving the quality of early childhood education. The background of this research is based on the importance of early childhood education institutions as the main foundation in shaping children's character and basic abilities, especially in the midst of increasing demands on the quality of national education. Quality early childhood education is one of the important factors in supporting children's optimal growth and development from an early age, both from cognitive and emotional aspects. This study uses a descriptive qualitative approach with observation techniques, in-depth interviews, and documentation as the main methods in data collection. The research subjects included school principals, teachers, and parents of students at KB El-Diina Sukabumi who were selected purposively in accordance with the research objectives. The results of the study show that KB El-Diina has implemented various strategies in improving the quality of educational services, including the implementation of a character-based curriculum, regular teacher training, active involvement of parents in the learning process, and the creation of a safe, comfortable, and fun learning environment for children. In addition, the use of learning methods that are in accordance with the child's developmental stage is also one of the success factors of the institution in improving the quality of education. The findings show that these efforts have a positive impact on children's cognitive, social, emotional, and motor development. Children look more confident, independent, and active in daily learning activities in the classroom and outdoors. The implications of this study emphasize the importance of professional, sustainable, and adaptive management of family planning institutions to the needs of children's development. This is the foundation for creating quality, relevant, and holistic child development early childhood education services.